2018
DOI: 10.1021/acsomega.7b01993
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Flow Preferential Hydrogenation of an Octanal/Octene Mixture Using Cu/Al2O3 Catalysts

Abstract: γ-Alumina-supported catalysts with varying copper loadings (5–25 wt %) were prepared by incipient wet impregnation and characterized by various characterization techniques. These catalysts were tested for the selective hydrogenation of octanal in a mixture containing 10 wt % octanal and 2 wt % octene diluted in octanol. The reactions were carried out in a continuous flow fixed-bed reactor in a down flow mode with varying pressures, liquid hourly space velocities, and hydrogen (H 2 )-to-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 57 publications
0
12
0
Order By: Relevance
“…Other reported Cu‐based catalysts in continuous‐flow hydrogenation of carbonyl compounds are based on Cu/Al 2 O 3 . Selective hydrogenation of an octanal/octene mixture (consisting of 10 wt % octanal and 2 wt % octene in octanol) using Cu/Al 2 O 3 catalysts was demonstrated by Friedrich and co‐workers . The results showed that Cu/Al 2 O 3 hydrogenated the aldehyde 70 preferentially and that the activity of the catalyst was related to the number of intermediate acid strength sites but not to the Cu content, specific surface area, and pore volume.…”
Section: Continuous‐flow Hydrogenation Using Heterogeneous Catalystsmentioning
confidence: 99%
“…Other reported Cu‐based catalysts in continuous‐flow hydrogenation of carbonyl compounds are based on Cu/Al 2 O 3 . Selective hydrogenation of an octanal/octene mixture (consisting of 10 wt % octanal and 2 wt % octene in octanol) using Cu/Al 2 O 3 catalysts was demonstrated by Friedrich and co‐workers . The results showed that Cu/Al 2 O 3 hydrogenated the aldehyde 70 preferentially and that the activity of the catalyst was related to the number of intermediate acid strength sites but not to the Cu content, specific surface area, and pore volume.…”
Section: Continuous‐flow Hydrogenation Using Heterogeneous Catalystsmentioning
confidence: 99%
“…Water impact studies were carried out at 160 • C and with a hydrogen-to-aldehyde ratio of 2 (H 2 :octanal, 2:1). These conditions were established in a previous study as the optimum for octanal conversion and octanol selectivity [25]. Once steady-state conversion was reached using the fresh feed, the water-spiked feed was introduced to the system.…”
Section: Catalytic Testing-water Impact Studiesmentioning
confidence: 99%
“…These processes involve the calcination or thermal reduction of nanoparticles, which consequently affect the metal electronic configuration, surface area, particle size, morphology, and reducibility. Among these MMOs, Cu-Al 2 O 3 nanoparticles, fabricated by solvent-deficient precipitation methods, have gained great attention in catalytic hydrogenation applications. For instance, the octanal conversion efficiency of up to 99% from a mixture of octanal and octene using the Cu-Al 2 O 3 catalyst has been achieved because the unpaired electrons in the d -band of copper adsorb hydrogen to promote catalytic efficiency . So far, very few studies have attempted the synthesis of Cu-Al 2 O 3 nanoparticles from the CuAl-LDH precursor.…”
Section: Introductionmentioning
confidence: 99%
“…11−13 For instance, the octanal conversion efficiency of up to 99% from a mixture of octanal and octene using the Cu-Al 2 O 3 catalyst has been achieved because the unpaired electrons in the d-band of copper adsorb hydrogen to promote catalytic efficiency. 11 precursor. Many catalytic reactions were shown to be temperature-dependent and were typically heated with the aid of external, low-efficient, and high energy-demanding radiative heat transfer processes.…”
Section: ■ Introductionmentioning
confidence: 99%